Involvement of secondary metabolites and extracellular lytic enzymes produced by plant growth promoting rhizobacteria in inhibiting the soilborne pathogens in Faba Bean Plants - Manal Sayed Mohammed Khalil; Mohamed Hassan Abdel-Rahem Hassan; Amer Fayz Mahmoud; Kadry Mostafa Mohamed Morsy (Universitas Lampung, 2022)
Plant growth promoting rhizobacteria (PGPR) viz. Pseudomonas fluorescens, Bacillus megaterium, B. subtilis, and B. cereus and their metabolic products may play a pivotal role in controlling root rot and wilt diseases in faba bean plants caused by Rhizoctonia solani, Fusarium solani, F. oxysporum, and Macrophomina phaseolina and promote plant growth under greenhouse and field conditions. Cell cultures, extracellular metabolites, volatile metabolites of all tested PGPR strains were suppressed the linear growth of all tested pathogenic fungi in vitro. P. fluorescens followed by B. megaterium were more active than B. subtilis and B. cereus in reduction of the tested fungi radial growth. All PGPR strains were able to produce IAA, HCN, siderophore, Ammonia in media growth. P. fluorescens produced the highest levels of cyanide hydrogen and ammonia followed by B. subtilis, while the higher level of IAA was produced by B. subtilis followed by P. fluorescens. Also, B. megaterium was the most PGPR strain produced siderophore followed by P. fluorescens. All the tested PGPR strains successfully solubilized inorganic phosphate on Pikovskya’s agar medium. Also, all plant growth promoting rhizobacteria strains (PGPR) were able to produce mycolytic enzymes viz. cellulase, chitinase ?-1,3-glucanase, amylase and protease except B. cereus and B. megaterium not able to produce protease and amylase. B. megaterium recorded the highest activities of chitinase, ?-1,3-glucanase, while, B. cereus produced the lowest levels of all tested enzymes.